SPK PENENTUAN PEMBERIAN PINJAMAN KEPADA ANGGOTA BUMDES DENGAN METODE SIMPLE ADDITIVE WEIGHTING - Nurul Putri Utami; Hasanul Fahmi; Anita Sindar (LPPM STMIK STIKOM Indonesia, 2019)
Information technology as a tool in the quality of manpower one of the world of government in the village, especially in the field of village-owned enterprises which are still doing work with the manual system. In addition, where it really needs a decision support system to help human resources in utilizing technology to run a process quickly and efficiently. The approach to find the value of attribute weights, namely approaching the existence of subjective, objective approaches and approaches of integration between subjective and objective. Decision Support System Implementation with Simple Additive Weighting Method can be used to determine the granting of loans to members of BUMDes Maju Bersama by entering in the form of alternative data and then entering the weight value seen in the existing criteria, so that it can produce the calculation value and the ranking of the prospective loan recipient. This draft will show the final results of each member who will borrow funds, and the highest rating can be said of the members who will receive loan assistance, the lowest rating will be given the opportunity to make decisions later to receive loan assistance.